Buddhist Psychology Past Life Regression Therapy - Sriplung, Tayat (Journal of International Buddhist Studies, 2016)
The purpose of this study was to determine whether Past Life Regression Therapy using Buddhist Psychology Approach can lead to better quality of lives, more profound belief about karma, and better psychological well. This Quasi-experimental research with a control group is designed to use twenty individuals (N=20) aging between 25 and 60 working at ICC International Company Limited as the experimental group (E), and the control group (C) of twenty working individuals working at the same company. Each experimental participant underwent past life regression facilitated by trained professional for this purpose during three 2.5 hours therapy sessions, and 7 days of designed life improvement practice between each session. Over the period of 35 days, participants in the experimental group had better score in quality of life than those in the control group with level of confidence at 0.05. Within the experimental group, scores on law of karma belief as well as quality of life and psychological well-being improved significantly with level of confidence at 0.05. The roles of past life experiences and lessons learnt in past-life regression toward the altered behaviors and beliefs were also examined. Since the role of life improvement practice in the experimental group did not show significance to improved life quality compared to the control group, this may have implications for further research on how long participants should take.